Perencanaan Sistem Penyaluran Air Limbah (SPAL) Di Perumahan Mutiara Permai Kota Pekanbaru - Syadli, Yudhi Hanafi; Asmura, Jecky; Elystia, Shinta (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
Mutiara Permai Recident do not have sewerage system facilities and on site sanitation systems. To solve this problems, planned a sewerage system and treatment of domestic wastewater is needed. The plan location consisting of 4 neighbourhood, service area covers the entire house totaling of 451 units. Sewerage system for residential use shallow sewer system that is domestic waste water (gray water and black water) directly connected using waste water pipes and sewerage systems with gravity system. Pipe dimensions is 100 mm for the waste water from the persil pipeline, 150 mm for service pipeline, 200 mm up to 560 mm for lateral pipelines, 560 mm for distributary pipeline and 800 mm for the main pipeline leading to the wastewater treatment plant (WWTP). For the continuity sewerage used manhole about 28 units.Keyword: Mutiara Permai Recident, Wastewater Domestic, SPAL